2016
DOI: 10.1155/2016/8742562
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect ofLoranthus parasiticuson IgE-Mediated Allergic Responses in RBL-2H3 Cells

Abstract: The mistletoe Loranthus parasiticus has been used as a compound for traditional medicine in Northeast Asia for a long time and is known to possess neuroprotective action. Nonetheless, the effect of Loranthus parasiticus on allergic responses remains unknown. In the present study, we evaluated whether the water extract of Loranthus parasiticus (LPE) could inhibit IgE-mediated allergic responses in RBL-2H3 cells. LPE inhibited the release of β-hexosaminidase (IC50, 184.5 μg/mL) and the formation of tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Histamine, secreted with β-hexosaminidase from mast cells, induces allergic inflammation, resulting in chronic allergic symptoms such as atopy, asthma, etc. Recent studies have reported the suppressive effects of flavonoids [21,22] and plant extracts [17] on mast cell degranulation. Among the various bioactive plant materials, Actinidia arguta extract has been recognized as a functional ingredient in facilitating the prevention of atopy, food allergy and asthma [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Histamine, secreted with β-hexosaminidase from mast cells, induces allergic inflammation, resulting in chronic allergic symptoms such as atopy, asthma, etc. Recent studies have reported the suppressive effects of flavonoids [21,22] and plant extracts [17] on mast cell degranulation. Among the various bioactive plant materials, Actinidia arguta extract has been recognized as a functional ingredient in facilitating the prevention of atopy, food allergy and asthma [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Following the immediate histamine release subsequent to antigen-mediated FcεRI aggregation, degranulation of mast cells results in the secretion of inflammatory mediators, including TNF-α, IL-4, leukotrienes and prostaglandins, which play key roles during the late phase of inflammatory reactions [16,17]. Inhibiting these mediators from activated mast cells is considered a promising strategy to ameliorate allergic responses.…”
Section: Effects Of Tricin and Etzl On The Secretion Of Cytokines And Lipid Mediatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such effects of Viscum coloratum are associated with some bioactive compounds including flavonoids, lectins, phenolic compounds, sesquiterpene lactones, terpenes, and viscotoxins [ 9 , 10 , 11 , 12 , 13 ]. Recently, we showed that the aqueous extract of Loranthus parasiticus had anti-allergic actions in the IgE/Ag-mediated allergic responses in mast cells [ 23 ]. Moreover, activation of IgE-sensitized mast cells in articular tissues is associated with the initiation and/or aggravation of osteoarthritic diseases including rheumatoid arthritis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%